2018
DOI: 10.1080/07060661.2017.1421588
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neofabraea actinidiae and N. brasiliensis as causal agents of apple bull’s-eye rot in southern Brazil

Abstract: The causal agents of apple bull's-eye rot in southern Brazil have recently been described as Neofabraea actinidiae and N. brasiliensis. Isolates of both species were evaluated for response of mycelial growth index (MGI) to different temperatures, enzyme production, mycelial growth inhibition and effective concentrations (EC 50 and EC 100) of the fungicides triflumizole, pyrimethanil and thiophanate methyl, as well as aggressiveness on fruits of 'Fuji' hybrid and 'Pink Lady'. There was significantly lower mycel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The inoculated fruit is often kept at room temperature while infections develop. Lesions usually appear within a few days, and the damage can be scored within a week after inoculation, although slow-growing fungi like Neofabraea may require incubation for 15 days [ 39 ] or a whole month before symptoms have developed sufficiently [ 28 ]. In one approach, some fruits were wound-inoculated with Colletotrichum either at harvest or after three months of cold storage [ 30 ].…”
Section: Quantification Of Storage Rot Damagementioning
confidence: 99%
See 1 more Smart Citation
“…The inoculated fruit is often kept at room temperature while infections develop. Lesions usually appear within a few days, and the damage can be scored within a week after inoculation, although slow-growing fungi like Neofabraea may require incubation for 15 days [ 39 ] or a whole month before symptoms have developed sufficiently [ 28 ]. In one approach, some fruits were wound-inoculated with Colletotrichum either at harvest or after three months of cold storage [ 30 ].…”
Section: Quantification Of Storage Rot Damagementioning
confidence: 99%
“…Similarly, small pieces of mycelia from N. alba have been inserted as plugs into fruit flesh, or placed in pockets under the skin of the fruit [40,45]. In a slightly modified version, fruit pulp plugs (5 × 3 mm) were extracted from detached fruit and replaced with equal-sized mycelial plugs of 21-day old Neofabraea cultures, covered by moist cotton and sealed with Parafilm [39]. Significant differences in lesion size were found among the inserted fungal isolates, but not between the two apple cultivars.…”
Section: Quantification Of Storage Rot Damagementioning
confidence: 99%
“…The effects of five culture media (MEA, PDA, TA, PCA (potato-carrot agar; 250 g potato, 200 g carrot, 17 g agar, 1 L of H 2 O)) and OA (oatmeal agar: 30 g oatmeal, 17 g agar, 1 L H 2 O)), eight temperatures (0, 5, 10, 15, 20, 25, 30, 35 • C) and nine pH levels (2,3,4,5,6,7,8,9,10) of MEA medium on the mycelial growth rate of representative isolates of each group were studied. The pH level of the MEA medium was adjusted with 0.1 M KOH and 0.1 M HCl (adjusted after sterilization of culture media).…”
Section: Physiological Characterizationmentioning
confidence: 99%
“…), Neofabraea sp. nov. (anamorph: C. kienholzii Seifert, Spotts and Levesque), and two species recently described as apple pathogens Neofabraea actinidiae and Neofabraea brasiliensis [4]. N. alba has been identified in European countries such as Poland, the Czech Republic, Italy, the Netherlands, and Spain as a causal agent of Bull's eye rot [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown the pathogen is highly susceptible (EC 50 <1 mg/L) to thiophanate methyl, pyrimethanil and triflumizole (Bogo et al 2018) but restrictions on the application of fungicides to fruit after flowering eliminates this as a management option in New Zealand kiwifruit.…”
Section: Management Strategiesmentioning
confidence: 99%